Air Flow Experiments on a Train Carriage—Towards Understanding the Risk of Airborne Transmission - Huw Woodward; Shiwei Fan; Rajesh K. Bhagat; Maksim Dadonau; Megan Davies Wykes; Elizabeth Martin; Sarkawt Hama; Arvind Tiwari; Stuart B. Dalziel; Roderic L. Jones; Prashant Kumar; Paul F. Linden (Atmosphere, 2021)
A series of experiments was undertaken on an intercity train carriage aimed at providing a “proof of concept” for three methods in improving our understanding of airflow behaviour and the accompanied dispersion of exhaled droplets. The methods used included the following: measuring CO2 concentrations as a proxy for exhaled breath, measuring the concentrations of different size fractions of aerosol particles released from a nebuliser, and visualising the flow patterns at cross-sections of the carriage by using a fog machine and lasers. Each experiment succeeded in providing practical insights into the risk of airborne transmission. For example, it was shown that the carriage is not well mixed over its length, however, it is likely to be well mixed along its height and width. A discussion of the suitability of the fresh air supply rates on UK train carriages is also provided, drawing on the CO2 concentrations measured during these experiments.